1998
DOI: 10.1177/107319119800500406
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of Neuropsychological Tests in Schizophrenia

Abstract: Validity studies of neuropsychological tests have typically examined individuals with neurological disorders. The present study was designed to investigate the construct validity of neuropsychological measures in patients with schizophrenia. We used Wechsler Adult Intelligence Scale Revised (WAIS-R) factor scores that were generated from the population of interest as marker variables in the present analysis. The current study included 39 patients with schizophrenia who were evaluated with a battery of neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Factor analytic studies of earlier editions of the WAIS found factor structures for psychiatric samples that corresponded reasonably well with those identified for the general population (Atkinson & Cyr, 1984;Beck, Horwitz, Seidenberg, Parker, & Frank, 1985;Cohen, 1952;Fowler, Zilmer, & Macciocchi, 1990;Piedmont, Sokolove, & Fleming, 1992). In the only examination of the factor structure of the WAIS-R in a schizophrenia sample, Allen and coworkers (Allen, Aldarondo, et al, 1998; identified Verbal Comprehension, Perceptual Organization, and "Freedom From Distractibility" factors, largely consistent with the structure most often proposed for nonclinical groups on the WAIS-R (see Hill, Reddon, & Jackson, 1985;Leckliter, Matarazzo, & Silverstein, 1986;Waller & Waldman, 1990).…”
mentioning
confidence: 59%
“…Factor analytic studies of earlier editions of the WAIS found factor structures for psychiatric samples that corresponded reasonably well with those identified for the general population (Atkinson & Cyr, 1984;Beck, Horwitz, Seidenberg, Parker, & Frank, 1985;Cohen, 1952;Fowler, Zilmer, & Macciocchi, 1990;Piedmont, Sokolove, & Fleming, 1992). In the only examination of the factor structure of the WAIS-R in a schizophrenia sample, Allen and coworkers (Allen, Aldarondo, et al, 1998; identified Verbal Comprehension, Perceptual Organization, and "Freedom From Distractibility" factors, largely consistent with the structure most often proposed for nonclinical groups on the WAIS-R (see Hill, Reddon, & Jackson, 1985;Leckliter, Matarazzo, & Silverstein, 1986;Waller & Waldman, 1990).…”
mentioning
confidence: 59%
“…These differences in battery composition may cause substantial changes in factor pattern results (Gorsuch 1974). Many previous studies have focused on the Wechsler Intelligence or Memory Scales (WISC, WAIS, or WMS) (Larrabee et al 1983; Bornstein and Chelune 1988; Allen et al 1998 a , 1998 b ) or have focused primarily on specific cognitive abilities (Sullivan et al 1993; Lieh-Mak and Lee 1997), such as memory (Compton and Adams 1992), rather than more comprehensive neuropsychological functioning. Nonetheless, where the batteries do overlap, certain common factors emerge across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Few factor-analytic studies have looked at larger neuropsychological batteries that include both memory and nonmemory tests. Nonetheless, when the results of various factor-analytic studies are examined, a number of common themes emerge, including verbal ability/language skills (Larrabee et al 1983; Woodcock and Johnson 1989; Moehle et al 1990; Heaton et al 1995; Allen et al 1998 a ; Ponton et al 2000); visual-spatial/perceptual-motor skills (Larrabee et al 1983; Woodcock and Johnson 1989; Moehle et al 1990; Heaton et al 1995; Allen et al 1998 a ); speed of information processing (Larrabee et al 1983; Woodcock and Johnson 1989; Heaton et al 1995); attention/concentration/working memory (Skilbeck and Woods 1980; Leonberger et al 1981; Larrabee et al 1983; Bornstein and Chelune 1988; Compton and Adams 1992; Heaton et al 1995); learning and memory (Skilbeck and Woods 1980; Larrabee et al 1983; Woodcock and Johnson 1989; Heaton et al 1995); psychomotor skills (Ponton et al 2000); and reasoning/abstraction (Leonberger et al 1981). While some studies have found separate verbal and visual learning and memory factors (e.g., Compton and Adams 1992; Moore and Baker 1997), not all studies included enough memory tests to look at verbal and visual abilities individually.…”
mentioning
confidence: 99%
“…The primary endpoint was derived from 8 computerized neurocognitive tests chosen for the specific aspects of cognitive performance that are measured by each test. The tests included: (1) AX Continuous Performance Test 18,19 ; (2) Identical Pairs Continuous Performance Test, 4-digit version 20-22 ; (3) Flanker Continuous Performance Test 23 ; (4) Auditory Digit Span [24][25][26][27] ; (5) Auditory Number Sequencing 28 ; (6) Strategic Target Detection 29,30 ; (7) Word List Memory 31,32 ; and (8) Symbol Digit Substitution. 33,34 Each test generates a series of dependent variables (e.g., reaction time, ability to distinguish targets from nontargets, total experiment time, and number of correct responses).…”
Section: Cognitive Testsmentioning
confidence: 99%